IC 8927 Helium Resources Of The United States, 1981 - Floyd R. Hertweck (The National Institute for Occupational Safety and Health (NIOSH), 1983)
The helium resources of the United States were estimated by the Bureau of Mines to be 1,037 Bcf as of January 1, 1981. These resources are divided into four categories, in decreasing degree of assurance of their existence: (1) helium in storage and in measured natural gas reserves, which totals 211 Bcf, (2) helium in indicated natural gas resources, which is estimated at 207 Bcf, (3) helium in hypothetical natural gas resources, which is estimated to be 318 Bcf, and (4) helium in speculative natural gas resources, which makes up the remaining 301 Bcf. These helium resources are further divided into depleting, nondepleting, and stored classifications, The depleting resources are those associated with natural gasfields that are, or will be, produced for the natural gas they contain. All of the helium in undiscovered (hypothetical and speculative) natural gas resources is included in this classification. These depleting resources are estimated to contain 897 Bcf of the total helium resource base. Nondepleting resources are those in shut-in, abandoned, or otherwise nonproducing natural gasfields. Helium resources contained in nondepleting natural gas resources are estimated to total 100 Bcf. There is 40 Bcf of helium in storage in the Federal Government-owned Cliffside Gas Field near Amarillo, Tex.